Peran Pendidikan Agama Islam sebagai landasan etika bermedia sosial - Mailita; Maisarah (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2024)
The development of science and technology has a significant impact on people's lives, especially students as digital natives and active internet users. Islamic Religious Education as one of the buffers in recognizing the limits in adapting to the latest conditions has a very important role in ethics in social media. This research uses descriptive quantitative and qualitative research (mixed method), the data collection techniques used are surveys, questionnaires and interviews, The sample in this study were 157 Lambung Mangkurat University students aged between 17-20 years. From the questionnaire distributed through google form, the results show that all students use social media, the platforms they use the most or more than 90% are WhatsApp and Instagram. The results showed that 18% of students had been victims of social media crimes such as cyberbullying, 15% claimed to have spread information whose sources were unclear or hoax news, and 13% had made negative comments or cyberbullying on social media. More than 60 percent of students know the ethics of using social media wisely according to Islamic teachings through Islamic Religious Education.